A YORÙBÁ PERSPECTIVE ON W. V. O. QUINE’S INDETERMINACY OF TRANSLATION THESIS (2021)
Indeterminacy, a condition of instability of meaning, uncertainty and variations in interpretations of grammatical forms and categories in any natural language, has generated both linguistic and philosophical challenges among scholars. Previous studies have examined the problem of translation using the theories of conceptual relativism and universalism. These theories however failed to provide enough bases for resolving the dilemma of cross-cultural understanding. This is due to the conflicting nature of the principles they articulate and their disregard for the skill of the translator and the purpose of the translation as important factors for providing purposeful action. This study, therefore, uses a Yoruba pragmatic perspective to interrogate the ‘Indeterminacy Thesis,’ with a view to determining the crucial role of the translator in translation. Hans Josef Vermeer’s Skopos Theory, which emphasises the communicative purpose in translation, was adopted as the framework, while the interpretive design was used. The texts used in Philosophy of Language included W. V. O. Quine’s Word and Object (WO) and Ontological Relativity (OR), Donald Davidson’s On the Very Idea of Conceptual Scheme (OVICS), Thomas Kuhn’s The Structure of Scientific Revolution (SSR) and George Steiner’s After Babel (AB). The texts used in African Philosophy included Kwasi Wiredu’s Cultural Universal and Particular (CUP), Isola Bewaji’s African Language and Critical Discourse (ALCD) and Segun Gbadegesin’s African Philosophy (AP). These texts deal extensively with the idea of culture, translation and cross-cultural understanding. The texts were subjected to the conceptual, critical and reconstructive tools of philosophy. The WO and OR revealed that the totality of intrinsic and extrinsic approaches to translating from one language into another fails to determine a unique system of translation. These approaches are inadequate because of their disregard for the linguistic skill and cultural background of the translator as well as the purpose of the translation. Variations in socio-cultural contexts make it fundamental that what needed to be translated is meaning rather than language (OVICS and SSR). The CUP and AB demonstrated that in the translation process, contextual factors cannot be overlooked. A meaningful translation requires the translator to determine the purpose of translation and the most suitable method for achieving it. The AP and ALCD showed that in Yoruba linguistic philosophy, translation is not only a linguistic act but also a cultural one. It is the intricate relationship between language and culture that shapes reality. Critical intervention revealed that the Yoruba indigenous education system, which deployed pragmatic and functional means to denote the essence of concepts as a product of culture, bridges the gap in translation created by other linguistic approaches. This system enables the translator to factor context and culture into the translation process. It also readily absorbs necessary linguistic elements from other cultures. The Yoruba linguistic philosophy provides a pragmatic understanding of translation which privileges the linguistic skill and cultural intelligence of the translator, and the objective of the translation. This provides one framework for undermining the indeterminacy thesis of W. V. O. Quine.